An Advanced Switching Harmonic Cancellation Method for a Dual-Generator Power System in More-Electric Aircraft - Wang, Cheng; Yang, Tao; Lang, Xiaoyu; Bozhko, Serhiy (IEEE journal of emerging and selected topics in power electronics, 2022)
Dual-generator power systems have attracted increased attention in recent years as it can significantly reduce the fuel assumption of aircraft engines allowing power transfer between different engine shafts. In such a system, two generators supply a common dc bus together. A dc-bus capacitor is required to filter switching harmonics to ensure that the dc-bus voltage satisfies the MIL-STD-704F standard. Due to the high current rating, this capacitor is normally bulky and heavy. This article aims to introduce a switching harmonic cancellation method, which can effectively reduce harmonics at the dc bus. This, in return, will extend the lifetime and reduce the weight of the dc-bus capacitor. With the assumption that power converters connected to the dc bus are modulated with the commonly used space vector pulsewidth modulation (SVPWM) technique, a simplified mathematical model to estimate both first and second switching harmonics is developed. Based on the proposed models, an advanced method of switching harmonic cancellation scheme is proposed through an adaptive phase shift of carrier signals for different power outputs of converters. Both simulation and experimental results are used to validate the proposed model and the suppression method.